CTL Attenuation Regulated by PS1 in Cancer-Associated Fibroblast - Zhang, Hongyu; Jiang, Rong; Zhou, Jinhua; Wang, Juan; Xu, Yuejuan; Zhang, He; Gu, Yanzheng; Fu, Fengqing; Shen, Yu; Zhang, Guangbo; Feng, Lanlan; Zhang, Xueguang; et al. (Frontiers in Immunology, 2020)
Objective: Cancer-associated fibroblasts (CAFs) was associated with tumor progression in the tumor microenvironment (TME). However, their immunosuppressive roles in protecting cancer cells from the attack by cytotoxic T lymphocytes (CTLs) are not fully clear. In this study, we investigated whether and how CAFs regulate tumor-infiltrating lymphocytes as well as their role in tumor immunosuppression. Methods: Eighty-three cases of ovarian cancer and 10 controls were analyzed for CAFs and CD8+ tumor-infiltrating lymphocytes by gene array and immunohistochemistry. We evaluated Presenilin 1 (PS1) expression in CAFs, CTL penetration, tumor burden, dendritic cell function, and migration of tumor-infiltrating lymphocytes and their function in vivo and in vitro after silencing PS1. In addition, the pathway via which PS1 affects the TME was also evaluated. Results: PS1 was highly expressed in CAFs, and its silencing significantly promoted CD8+ CTL proliferation and penetration in multiple ovarian models (p＜0.05), resulting in tumor regression and growth inhibition. IL-1β was identified as a major immune inhibitor in the TME, and it was significantly decreased after PS1 silencing (p＜0.05), which was regulated by the WNT/β-catenin pathway. It was also showed that high expression of IL-1β in CAFs inhibits CTL penetration significantly (p＜0.05). Conclusion: Highly expressed PS1 in CAFs plays a crucial role in regulating tumor-infiltrating lymphocyte populations in the TME via the WNT/β-catenin pathway. Targeting PS1 may retrieve functional CTLs in the TME and improve the efficacy of current immunotherapies.